Versatile Double Bandgap Photonic Crystals of High Color Saturation - Hao Jiang; Gang Li; Luying Si; Minghui Guo; Huiru Ma; Wei Luo; Jianguo Guan (Nanomaterials, 2023)
Double bandgap photonic crystals (PCs) exhibit significant potential for applications in various color display-related fields. However, they show low color saturation and inadequate color modulation capabilities. This study presents a viable approach to the fabrication of double bandgap photonic inks diffracting typical secondary colors and other composite colors by simply mixing two photonic nanochains (PNCs) of different primary colors as pigments in an appropriate percentage following the conventional RGB color matching method. In this approach, the PNCs are magnetically responsive and display three primary colors that can be synthesized by combining hydrogen bond-guided and magnetic field (H)-assisted template polymerization. The as-prepared double bandgap photonic inks present high color saturation due to the fixed and narrow full-width at half-maxima of the parent PNCs with a suitable chain length. Furthermore, they can be used to easily produce a flexible double bandgap PC film by embedding the PNCs into a gel, such as polyacrylamide, facilitating fast steady display performance without the requirement of an external magnetic field. This research not only presents the unique advantages of PNCs in constructing multi-bandgap PCs but also establishes the feasibility of utilizing PNCs in practical applications within the fields of anti-counterfeiting and flexible wearable devices.